(3TQM edMI GdEYQGHs - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hGdUdGI hGdSdGe Ydi SjOfG eMeO hBdg hUMHg NjQ YHGO Gddg gPg deMI aj TQM GdedMI jfJaY HgG GdWGdH hjgJOj HgG GdQGZHs
(3BNQgG (B:s
(3HYO MeO GdUeO YhOG Ydi HOA Ydi GdfHj GdeUWai GdeNJGQ eMeO hBdg CbGQHg GdeDefjf ef Hfj gGTe hGdeWdH hUMHg GdPjf GLJeYhG Hg aj MjGJg eDefjf GdCNjGQ LeY NjQ GdbGfJjf GdeWjYjf ddg JYGdis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 3 / 301s
(3eYLe GdeDdajf(B: 2 / 82s
(3cTa GdXfhf(B: 2 / 1817s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs